DINAMIKA PEMBENTUKAN DAN IMPLEMENTASI UU PORNOGRAFI DALAM KONTEKS POLITIK HUKUM INDONESIA - Roidatus Shofiyah (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This article discusses the dynamics of the formation and implementation of the Pornography Law in Indonesia within the context of legal politics. The law, which was enacted in 2008, went through a lengthy process that began in 1997 and faced opposition from various groups, including local communities with diverse cultural backgrounds. A major challenge in its implementation is the misalignment with local cultural values, as well as the broad and ambiguous definition of pornography, which complicates law enforcement—particularly in the digital era. The type of research used is normative legal research, which includes the study of legislation, comparative law, and legal history. This article concludes that in order to ensure effective implementation, the Pornography Law must be adjusted to accommodate cultural diversity and evolving societal developments, rather than relying heavily on other regulations such as the ITE Law, the TPKS Law, and the Criminal Code (KUHP). In addition, collaboration between the government, society, and legal institutions is essential.